Impact of pelvic rocking exercise on dysmenorrhea among adolescent girls - Saikia, Banashri; B., Bhavani B.; K., Logambal; S., Karpagam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Pelvic rocking exercise is an exercise which contracts deep abdominal muscles and buttocks by taking deep breath, so that a small movement takes place inside the uterus. It is an exercise which strengthens the muscles of lower abdomen and back by taking deep breath. So that the pressure on blood vessels in the area around uterus is relieved. It helps to relieve menstrual discomfort through increased vasodilatation and subsequent decreased ischemia, release of endogenous opiates and suppression of prostaglandins. It is a non-pharmacological management of dysmenorrhea. It increases endorphin release which decreases pain perception and to suppress prostaglandin release. It is found to be effective in managing stress and is easy to practice. Present study aimed to evaluated the effectiveness of pelvic rocking exercise on dysmenorrhea. Methods: Pre- experimental one group pre-test post-test design has been used to attain the objectives of the present study. 60 adolescent girls were selected by non- probability purposive sampling technique. Sociodemographic variables, menstrual history related data was collected and standardized Numerical Pain Rating Scale was used to assess the level of dysmenorrhoea among adolescent girls. Pelvic rocking exercise was the intervention done to evaluate its effect on the level of dysmenorrhea. Results: Out of total adolescent girls, majority had moderate level of dysmenorrhea. There was a significant difference between the pre and post- intervention level of dysmenorrhoea. Conclusions: Study concluded that the intervention of pelvic rocking exercise was significantly effective in reduction of dysmenorrhoea among the adolescent girls.